How to design font size for older adults: A systematic literature review with a mobile device - Hou, Guanhua; Anicetus, Umenwaniri; He, Jingwei (Frontiers in Psychology, 2022)
With the global society ageing, it is necessary to investigate suitable font size based on reading time/speed, readability and legibility for older adults. This study used a systematic review of previous and existing relevant research on font size for older adults and research on the psychophysics of reading and analyzed the outcomes based on reading time/speed, readability, legibility and the usability evaluation methods employed. Studies were selected from databases GOOGLE SCHOLAR, WEB OF SCIENCE, PUBMED, and SCIENCE DIRECT. An inclusion criterion was used to remove duplicates and avoid inconsistencies. Results suggest that older adults preferred larger font sizes. However, there exists a critical size at which readability declines. Inconsistencies in evaluation methods and experimental procedures were observed in the selected articles. This study suggested a reusable catalogue of usability evaluation methods, eye tracking for user testing and a questionnaire for inquiry as suitable usability evaluation methods, a uniform metrics to measure font size (visual angle of font) in arcminutes and parameters to consider when investigating font size for older adults to ensure consistency in future studies.